Characterization of indigenous Durio species from Sarawak, Borneo: relationships between chemical composition and sensory attributes - Sujang, Gerevieve Bangi; Ramaiya, Shiamala Devi; Lee, Shiou Yih; Zakaria, Muta Harah (PeerJ Inc., 2024)
Sarawak, Borneo, harbours 16 unique Durio species, half of which are edible, with only Durio zibethinus widely cultivated. Despite their nutritional and economic significance to the rural communities in Sarawak, the lesser-known indigenous durians remain underrepresented in the scientific literature while facing the risk of extinction in the wild. Thus, the aim of this study was to conduct comprehensive chemical analyses of these wild edible durians, offering insights into their nutritional and sensory taste attributes. The edible part was separated at optimal ripeness, and the samples were subjected to further analysis. Wild edible durian genotypes exhibit varied characteristics, even within the same species. The majority of wild durians are characterized by a sugar composition consisting predominantly of sucrose, constituting 67.38–96.96%, except for the red-fleshed Durio graveolens renowned for its low total sugar content (0.49 ± 0.17 g per 100 g). Despite its bland taste, this species possessed significantly greater fat (14.50 ± 0.16%) and fibre (12.30 ± 0.14%) content. Durio dulcis exhibited a significantly greater carbohydrate content (29.37–30.60%), and its intense smell was attributed to its low protein content (2.03–2.04%). Indigenous durians offer substantial percentages of daily mineral intake, with 100 g servings providing approximately 15.71–26.80% of potassium, 71.72–86.52% of phosphorus, 9.33–27.31% of magnesium, and sufficient trace minerals. The vibrant flesh colours of yellow-, orange- and red-fleshed Durio graveolens and Durio kutejensis show high levels of ascorbic acid (31.41–61.56 mg 100 g−1), carotenoids (976.36–2627.18 µg 100 g−1) and antioxidant properties, while Durio dulcis and Durio oxleyanus, despite their dull flesh, contained high phenolic (67.95–74.77 mg GAE 100 g−1) and flavonoid (8.71–13.81 QE mg 100 g−1) levels. These endeavours provide a deeper understanding of the nutritional richness of wild edible durians, thereby supporting commercialization and conservation efforts.